2009
DOI: 10.1007/s00114-009-0631-9
|View full text |Cite
|
Sign up to set email alerts
|

The alternative Pharaoh approach: stingless bees mummify beetle parasites alive

Abstract: Workers from social insect colonies use different defence strategies to combat invaders. Nevertheless, some parasitic species are able to bypass colony defences. In particular, some beetle nest invaders cannot be killed or removed by workers of social bees, thus creating the need for alternative social defence strategies to ensure colony survival. Here we show, using diagnostic radioentomology, that stingless bee workers (Trigona carbonaria) immediately mummify invading adult small hive beetles (Aethina tumida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 20 publications
3
54
0
3
Order By: Relevance
“…Taken together with earlier reports in honeybee, A. mellifera , colonies (Atkinson and Ellis 2011a, b), this suggests that this beetle species can exploit a variety of different social bee species. This is similar to the small hive beetle, which can infest colonies of honeybees (Neumann and Elzen 2004), bumblebees Bombus impatiens (Spiewok and Neumann 2006), as well as stingless bees Trigona carbonaria (Greco et al 2010) and Austroplebeia australis (Halcroft et al 2011). …”
supporting
confidence: 57%
“…Taken together with earlier reports in honeybee, A. mellifera , colonies (Atkinson and Ellis 2011a, b), this suggests that this beetle species can exploit a variety of different social bee species. This is similar to the small hive beetle, which can infest colonies of honeybees (Neumann and Elzen 2004), bumblebees Bombus impatiens (Spiewok and Neumann 2006), as well as stingless bees Trigona carbonaria (Greco et al 2010) and Austroplebeia australis (Halcroft et al 2011). …”
supporting
confidence: 57%
“…Plant resins are widely used in bee societies as honeybees and other bees share a common spectrum of diseases and predators. Stingless bees' resinous products have known antifungal effects (Aspergillus niger ) (Garedew et al 2003b;Muli et al 2008) and are highly effective when used to mummify A. tumida beetles by deposing resin on the body of the intruder (Greco et al 2010;Halcroft et al 2011). Comparative studies (single type resin vs. mixtures) revealed that single resins may have different effects, and mixtures are more effective indicating functional complementarity for repellent effects against predatory ants and A. tumida (Drescher et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of applied studies, monitoring of pest and invasive species (Fuchs et al., 2004; Halley et al., 2005; Harrison et al., 1993; Monaenkova et al., 2015; Soné, Mori, Ide, Setoguchi, & Yamanouchi, 1995; Tarver et al., 2006), interaction between hosts and parasites (Greco et al., 2010; Schwabe et al., 2014), forensic entomology (Johnson et al., 2012), and ecotoxicological research (Brinkmann et al., 2016; Holliday & Holliday, 2012; Lind et al., 2004; Pigneret et al., 2016; Yunusa, Braun, & Lawrie, 2009) have been also benefited greatly from this technique so far.…”
Section: Perspectives and Final Considerationsmentioning
confidence: 99%